Role of social support in poststroke depression: A meta-analysis - Bi, Haiyang; Wang, Mengjia (Frontiers in Psychiatry, 2022)
Poststroke depression significantly affects health and quality of life of stroke patients. This study evaluates the role of social support in influencing poststroke depression. The literature search was conducted in electronic databases and study selection was based on precise eligibility criteria. The prevalence rates reported by individual studies were pooled. A meta-analysis of standardized mean differences (SMD) in social support between depressed and non-depressed stroke patients was performed. The odds ratios and correlation coefficients showing the relationship between social support and depression were pooled to achieve overall estimates. Twenty-five studies (9431 patients) were included. The prevalence of depression was 36% [95% confidence interval (CI): 28, 45]. Patients with poststroke depression had significantly lower social support in comparison with patients with no or lower levels of depression (SMD in social support scores −0.338 [95% CI: −0.589, −0.087]; p=0.008). The odds of depression were lower in patients receiving higher levels of social support (OR 0.82 [95% CI: 0.69, 0.95]) but were higher in patients who were receiving weaker social support (OR 5.22 [95% CI: −0.87, 11.31]). A meta-analysis of correlation coefficients found a significantly inverse correlation between social support and poststroke depression (r −0.336 [95% CI: −0.414, −0.254]). Poststroke depression has a significant independent inverse association with social support.